Direct comparison of FRAXR and a simplified fracture risk assessment tool in routine clinical practice: a registry-based cohort study. Issue 9 (September 2016) - Leslie, W.; Majumdar, S.; Lix, L.; Josse, R.; Johansson, H.; Oden, A.; McCloskey, E.; Kanis, J.
Abstract Summary FRAXR incrementally improved prediction of incident major osteoporotic fractures compared with the simplified Canadian Association of Radiologists and Osteoporosis Canada (CAROC) tool. Introduction There is debate over the value of seemingly more complex fracture prediction tools over simpler fracture prediction tools. FRAXR and the simplified CAROC tool are both widely used in Canada for estimating 10-year probability of major osteoporotic fractures. We compared the performance of these tools for predicting fracture outcomes. Methods Using a bone densitometry registry for Manitoba, Canada, we identified 34, 060 individuals age ≥50 years not receiving anti-osteoporosis therapy. Fracture Risk Assessment (FRAX) and CAROC were used to classify 10-year fracture risk as low (<10 %), moderate (10–20 %) and high (>20 %). Net reclassification improvement (NRI) was used to quantify the performance of FRAX versus CAROC. Results During mean 9.8 years of follow-up, 3905 individuals sustained fractures. There were 10 (of 35 total) situations where observed fracture risk fell outside of the predicted range, and all 10 discordances favoured FRAX. NRI among incident fracture cases was not significantly changed, but there was a significant improvement in risk categorization for those who remained fracture-free (+1.7 %, P < 0.001) resulting in overall improvement (NRI overall +0.028, P < 0.001). Within nine pre-specified subgroups, there was no case of significant worsening in NRI when using FRAX instead of CAROC. In absolute terms, only 36 individuals would need to be assessed using FRAX instead of CAROC to yield an improvement in prediction (8 among individuals with prior fracture and 4 among those with prolonged glucocorticoid use). Conclusions FRAX provides improvement in fracture risk prediction compared with the simplified CAROC tool in individuals referred for osteoporosis screening, supporting the use of FRAX as the international reference tool for fracture risk assessment.